Environmental Effects on Thermal Properties of PEI/Glass Fiber Composite Materials - Botelho,Edson Cocchieri (2013)
ABSTRACT: The aim of this study was to investigate the effects of hygrothermal exposure, ultraviolet (UV) radiation, salt spray and thermal shock aging on the thermomechanical behavior of glass fiber reinforced by poly (ether-imide) (PEI) composites. Dynamic mechanical (DMA) and Thermomechanical (TMA) analyses have been performed on the aged PEI composites after being submitted to the climatic chambers. Additional techniques have been used to characterize the laminates, such as optical microscopy and infrared spectroscopy (FT-IR) in order to evaluate possible structural changes in these materials. Slight changes were observed both in glass transition temperature and in thermal expansion coefficient as a result from the environmental conditioning used (hygrothermal, salt spray, UV radiation and thermal shock conditioning). Thus, when exposed to these conditions, PEI/glass fiber laminates maintain its compromise with the performance component.